2018
DOI: 10.1108/ijqrm-02-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Slack resources and quality performance: case of a mega health care organization

Abstract: Purpose Prior studies have examined the relationship between budgetary slack and short-termism of management within a profit-seeking business environment. The purpose of this paper is to examine the dynamics of slack resources in relation to quality performance of heath care services delivered by a publicly funded organization. Design/methodology/approach A longitudinal regression analysis of resource utilization, productivity and the quality of health care services delivered is performed to reveal evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Early research has shown that maintaining a certain amount of slack resources can promote organizational performance and quality performance improvements (Bourgeois, 1981). However, through a survey of large medical institutions, Ng et al (2018) found that idle resources help improve productivity and services quality only under certain conditions. Taking the cost into account, the existence of slack is not conducive to overall performance improvement (Courty and Marschke, 2003;Daniel et al, 2004;Mohr and Young, 2012).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research has shown that maintaining a certain amount of slack resources can promote organizational performance and quality performance improvements (Bourgeois, 1981). However, through a survey of large medical institutions, Ng et al (2018) found that idle resources help improve productivity and services quality only under certain conditions. Taking the cost into account, the existence of slack is not conducive to overall performance improvement (Courty and Marschke, 2003;Daniel et al, 2004;Mohr and Young, 2012).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…From the lean manufacturing perspective, operational stickiness leads to resource slack, a type of waste which should be eliminated (Shah and Ward, 2003;Taj, 2008). As the agency theory points out, excessive slack leads to unnecessary empire building and reduces the performance and quality of delivering services to end users (Tan and Peng, 2003;Ng et al, 2018). Additionally, companies that over sticky cannot respond quickly to market changes (Azadegan et al, 2013), which may lead to a negative impact on quality performance.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Some argue that TQM is positively associated with organisational innovation, while others view this connection in negative terms (Carpenter, 2002;Lenka and Suar, 2008;Sila, 2007). Hence, "slack" as a concept is used to understand these debates in greater depth and to better underline this paradox (Ng and Wang, 2018). Innovation further requires a certain level of organisational performance and resource slack (Damanpour et al, 2009;Herold et al, 2006); however, it is also associated with trial and error, and demands time and resources to find and study new solutions (Mol and Birkinshaw, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Duh et al (2012) confirmed this finding by adding another condition, an organisation should be less leveraged to have more resources to implement TQM practices. Interestingly, slack resources were also suggested to enhance quality delivery beyond a short-term time frame, and were considered a "buffer" to achieve a specific target (Ng and Wang, 2018). Given that TQM approaches need to change to further support continuous innovation, an investigation on slack itself remains important (Steiber and Alänge, 2013;Liu et al, 2017).…”
mentioning
confidence: 99%
“…Within the healthcare industry, prior research suggests that slack staff levels have important performance implications (Mallidou et al , 2011). For example, research suggests a positive relationship between expenditures and quality (Valdmanis et al , 2008) as well as positive relationship between medical staff and reducing patient complaints (Ng and Wang, 2018). However, other research shows a negative relationship between spending and patient outcomes (Fisher et al , 2003a, b).…”
Section: Introductionmentioning
confidence: 99%